Efektivitas Pemungutan Pajak Reklame terhadap Peningkatan Pendapatan Asli Daerah Kota Makassar - Karmilah Karmilah; Hasrillah Hasrillah (YUME : Journal of Management, 2021)
AbstarctThis study aims (1) to find out how the effectiveness of the collection of Advertising Tax on Regional Original Revenue of Makassar City. (2) To find out what are the obstacles to collecting Advertising Tax by the Makassar City Regional Revenue Agency.The type of research used is qualitative research with data collection techniques through observations, interviews and documentation with data analysis using Data Reduction, Data Presentation and Conclusion Drawing and Verification techniques. The results of the study indicate that the collection of Advertising Tax is quite effective in increasing Makassar City's Original Regional Revenue. The effectiveness of advertising tax collection has increased from year to year. In 2017, the level of effectiveness of collecting advertisement tax from the realization received experienced a significant increase of 160.25% (very effective). Likewise, in 2018 the level of effectiveness of collecting advertisement tax from the realization received was 118.11% (very effective). And in 2019 the level of effectiveness of collecting advertisement tax from realization was 101.21% (very effective). And in 2020 the level of effectiveness of collecting Advertising Tax from realization is 113.68%. Keywords: Effectiveness, Collection, Advertising Tax, Local Revenue.